3CLpro inhibitors: DEL-based molecular generation - Xiong, Feng; Xu, Honggui; Yu, Mingao; Chen, Xingyu; Zhong, Zhenmin; Guo, Yuhan; Chen, Meihong; Ou, Huanfang; Wu, Jiaqi; Xie, Anhua; Xiong, Jiaqi; Xu, Linlin; et al. (Frontiers in Pharmacology, 2022)
Molecular generation (MG) via machine learning (ML) has speeded drug structural optimization, especially for targets with a large amount of reported bioactivity data. However, molecular generation for structural optimization is often powerless for new targets. DNA-Encoded Libraries (DEL) can generate systematic, target-specific activity data, including novel targets with few or unknown activity data. Therefore, this study aims to overcome the limitation of molecular generation in the structural optimization for the new target. Firstly, we generated molecules using the structure-affinity data (2.96 million samples) for 3C-like protease (3CLpro) from our own-built DEL platform to get rid of using public databases (e.g., CHEMBL and ZINC). Subsequently, to analyze the effect of transfer learning on the positive rate of the molecule generation model, molecular docking and affinity model based on DEL data was applied to explore the enhanced impact of transfer learning on molecule generation. In addition, the generated molecules are subjected to multiple filtering, including physicochemical properties, drug-like properties, and pharmacophore evaluation to determine the molecules for further study and verified by molecular dynamics simulation.